A Device-Independent Evaluation of Carbonyl Emissions from Heated Electronic Cigarette Solvents - Wang, Ping; Chen, Wenhao; Liao, Jiawen; Matsuo, Toshiki; Ito, Kazuhide; Fowles, Jeff; Shusterman, Dennis; Mendell, Mark; Kumagai, Kazukiyo (PLOS ONE, 2017)
Objectives To investigate how the two main electronic (e-) cigarette solvents—propylene glycol (PG) and glycerol (GL)—modulate the formation of toxic volatile carbonyl compounds under precisely controlled temperatures in the absence of nicotine and flavor additives. Methods PG, GL, PG:GL = 1:1 (wt/wt) mixture, and two commercial e-cigarette liquids were vaporized in a stainless steel, tubular reactor in flowing air ranging up to 318°C to simulate e-cigarette vaping. Aerosols were collected and analyzed to quantify the amount of volatile carbonyls produced with each of the five e-liquids. Results Significant amounts of formaldehyde and acetaldehyde were detected at reactor temperatures ≥215°C for both PG and GL. Acrolein was observed only in e-liquids containing GL when reactor temperatures exceeded 270°C. At 318°C, 2.03±0.80 μg of formaldehyde, 2.35±0.87 μg of acetaldehyde, and a trace amount of acetone were generated per milligram of PG; at the same temperature, 21.1±3.80 μg of formaldehyde, 2.40±0.99 μg of acetaldehyde, and 0.80±0.50 μg of acrolein were detected per milligram of GL. Conclusions We developed a device-independent test method to investigate carbonyl emissions from different e-cigarette liquids under precisely controlled temperatures. PG and GL were identified to be the main sources of toxic carbonyl compounds from e-cigarette use. GL produced much more formaldehyde than PG. Besides formaldehyde and acetaldehyde, measurable amounts of acrolein were also detected at ≥270°C but only when GL was present in the e-liquid. At 215°C, the estimated daily exposure to formaldehyde from e-cigarettes, exceeded United States Environmental Protection Agency (USEPA) and California Office of Environmental Health Hazard Assessment (OEHHA) acceptable limits, which emphasized the need to further examine the potential cancer and non-cancer health risks associated with e-cigarette use.